2019
DOI: 10.1038/s41467-019-09875-7
|View full text |Cite|
|
Sign up to set email alerts
|

High mitogenic stimulation arrests angiogenesis

Abstract: Appropriate therapeutic modulation of endothelial proliferation and sprouting is essential for the effective inhibition of angiogenesis in cancer or its induction in cardiovascular disease. The current view is that an increase in growth factor concentration, and the resulting mitogenic activity, increases both endothelial proliferation and sprouting. Here, we modulate mitogenic stimuli in different vascular contexts by interfering with the function of the VEGF and Notch signalling pathways at high spatiotempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
117
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(133 citation statements)
references
References 58 publications
15
117
1
Order By: Relevance
“…The formation of new blood vessels for tissue homeostasis requires a finely tuned temporal and spatial control of the biology of ECs. Among the cellular responses integrated during angiogenesis, cell growth, and division stand pivotal for the generation of a fully functional vascular plexus 16-18,20 . However, the molecular underpinnings of EC proliferation during angiogenesis remain scarcely known 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of new blood vessels for tissue homeostasis requires a finely tuned temporal and spatial control of the biology of ECs. Among the cellular responses integrated during angiogenesis, cell growth, and division stand pivotal for the generation of a fully functional vascular plexus 16-18,20 . However, the molecular underpinnings of EC proliferation during angiogenesis remain scarcely known 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, excessive EC proliferation as a result of notch inhibition gives rise to increased microvascular density but defective perfusion in tumors 16 and mice lacking Flt1 die of vascular overgrowth, 17 as a consequence of increased availability of VEGFA to bind to VEGFR2 18 . More recently, it has been demonstrated that an abnormally high mitogenic signal induced by the endothelial deletion of PTEN, 19 VEGFR2 gain‐of‐function or Notch loss‐of‐function 20 results in defective angiogenesis. Therefore, the mechanisms that ensure restriction of EC proliferation are fundamental; and a deep understanding of the pathways that fine‐tune EC proliferation during the remodeling of the vasculature could be relevant for a successful therapeutic suppression or stimulation of angiogenesis in pathological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In cdkn1a/p21 knockdown embryos, a greater number of ECs proliferate, while a reduction in vegfab signaling increases expression of cdkn1a/p21 and causes fewer ECs to proliferate. Recently, increases in ERK signaling were shown to upregulate cdkn1a/p21 expression in ECs in the mouse retina, resulting in cell cycle arrest (Pontes-Quero et al, 2019). Our results suggest that PI3K signaling downstream of vegfab similarly controls the amount and/or localization of cdkn1a/p21, thereby determining the amount of actively cycling ECs during angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For mouse retina immunostaining, eyes were collected at the indicated time points and fixed in 4% PFA in PBS for 1h at room temperature (RT). After two PBS washes, retinas were micro-dissected and stained as described previously (Pontes-Quero et al, 2019). Briefly, retinas were blocked and permeabilized with 0.3% Triton X-100, 3% FBS and 3% donkey serum in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Both in development 11,12 and pathologies 13,14 , VEGF stimulates both sprouting and growth of endothelial cells (ECs) and formation of new blood vessels, acting mainly through its receptor VEGFR2. Surprisingly however, a recent report demonstrated that high levels of VEGF-A in fact inhibit the proliferation of arterial tip cells in the postnatal mouse retina, while promoting their active migration and sprouting 15 . In contrast to these advances, little is known about the spatiotemporal dynamics of cell cycle progression in ECs in vivo and how it affects angiogenesis and sprouting.…”
Section: Introductionmentioning
confidence: 94%